2020
DOI: 10.1371/journal.pntd.0008046
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of Vibrio cholerae reveals the regional and global spread of two epidemic non-toxigenic lineages

Abstract: Non-toxigenic Vibrio cholerae isolates have been found associated with diarrheal disease globally, however, the global picture of non-toxigenic infections is largely unknown. Among non-toxigenic V. cholerae, ctxAB negative, tcpA positive (CNTP) isolates have the highest risk of disease. From 2001 to 2012, 71 infectious diarrhea cases were reported in Hangzhou, China, caused by CNTP serogroup O1 isolates. We sequenced 119 V. cholerae genomes isolated from patients, carriers and the environment in Hangzhou betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
5
22
1
Order By: Relevance
“…The case in the Chaco region during 2005, which was caused by non-epidemic V. cholerae O1 of the MX-2 lineage 7 and failed to cause epidemic cholera, exemplifies this point. Similar observations have recently been made in China 48 . Relative risk of V. cholerae lineages should be accounted for in the magnitude of epidemic preparedness responses to such outbreaks, as is now being done in Argentina.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The case in the Chaco region during 2005, which was caused by non-epidemic V. cholerae O1 of the MX-2 lineage 7 and failed to cause epidemic cholera, exemplifies this point. Similar observations have recently been made in China 48 . Relative risk of V. cholerae lineages should be accounted for in the magnitude of epidemic preparedness responses to such outbreaks, as is now being done in Argentina.…”
Section: Discussionsupporting
confidence: 90%
“…1 d, 4a, b ; Supplementary Data 3 ). Thus, we placed these into context with a more diverse collection of V. cholerae sequences 7 , together with genomes from a recently-published study of non-epidemic V. cholerae O1 in China 48 , and then calculated a pangenome using these sequences (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…We further compared the ST75 isolates from South Africa with a larger global collection of 144 ST75, or closely related ST169, ST170, and ST182, genomes (Appendix 2), and constructed a maximum-likelihood phylogeny by using 49,540 SNPs (Figure). Our phylogenetic analysis showed that the 7 isolates from South Africa clustered in the L3b.1 clade, defined by H. Wang et al (9), with a maximum pairwise distance of 22 SNPs. Isolates from Limpopo Province had a maximum pairwise distance of 1-6, but KwaZulu-Natal Province isolates had no SNP differences.…”
Section: The Studysupporting
confidence: 52%
“…All the software settings used were the default parameters, unless otherwise stated. A gene/segment was considered present if the overall hit coverage and identity were both ≥70 % [ 48 ].…”
Section: Methodsmentioning
confidence: 99%